Studentification in Conservative Turkish Cities: Towards A Nuanced Understanding of Resident Responses to Socio-Cultural Change - Islam, Tolga; Oztas, Doguscan; Tuncer-Tiryaki, Tugba (WILEY, 2026)
This study investigates the socio-cultural impacts of studentification in two conservative cities in Turkey - Erzurum and Konya, which serve as laboratories for understanding how university student populations interact with deeply traditional communities. Drawing on in-depth interviews with students and long-term residents between 2016 and 2025, we investigate how the rapid expansion of higher education in Turkey has transformed these religious and nationalist strongholds. The research uncovers distinct patterns of studentification in conservative contexts that challenge Western scholarship. While international literature primarily focuses on disruptive student behaviours generating town-gown tensions, our study demonstrates that in conservative settings, even mild forms of cultural difference - such as mixed-gender socialisation or non-traditional clothing - become sources of significant social friction. Paradoxically, student enclaves emerge as liberating spaces for local residents constrained by traditional norms, particularly women who gain expanded access to public life through new cultural spaces where secularisation processes become more visible and normalised.
Keywords: studentification; cultural negotiation; conservative cities; secularisation; moral panic; gender; GEOGRAPHIES; STUDENTS; UNIVERSITY; CITY; GENTRIFICATION; TOWN; SPATIALITIES; GENTRIFIERS; SEGREGATION; DISCOURSES; Business & Economics; Geography